Teacher’s questioning and students’ critical thinking in EFL classroom interaction - Yuliawati Yuliawati; Murni Mahmud; Muliati Muliati (Universitas Negeri Makassar, 2016)
The present study intended to examine the levels of questions based on Bloom’s Taxonomy used in EFL classroom interaction, to investigate the teacher’s questioning techniques and to analyze the roles of teacher’s questioning on students’ critical thinking. This study applied qualitative descriptive method. Classroom observation, field notes and interview were employed. The study engaged an English teacher at SMA Negeri 1 Tolitoli. The result showed that the teacher asked four out of six levels of questions. The teacher asked all lower-order levels questions (knowledge, comprehension and application) whereas he only asked fewer analysis questions as higher-order levels questions (never asked synthesis and evaluation questions). Furthermore, the teacher applied all questioning techniques proposed by Turney. They are structuring, focusing, redirecting, distributing, pausing, teacher reacting, prompting and changing the level of cognitive demand. This study also found the new technique, namely joking. However, the results revealed that the roles of teacher’s questioning only in the lower-order thinking of the students which could not facilitate the student’s critical thinking but it can lead the students to think critically. Therefore, it was recommended to maximize the use of higher-order levels questions in order to train the students think critically.Keywords: Lower-order levels questions, higher-order levels questions, questioning techniques, critical thinking